How did the urban and rural resident basic medical insurance integration affect medical costs?-Evidence from China. - Chen Liu; Qun Su; Meng Wang; Huaizhen Xing (PLoS ONE)
The Urban and Rural Residents' Basic Medical Insurance (URRBMI) aims to improve access to medical services, increase medical insurance benefits to reduce medical costs, and ultimately achieve medical equity. However, in the practice of the policy, the medical costs of Chinese residents have not been reduced. To assess the impact of URRBMI on Chinese residents' healthcare resource utilization and medical costs, this study explores the fixed-effects DID methodology using CHARLS data for 2013, 2015, 2018, and 2020, explains the reasons for the rise in healthcare costs in terms of two paths, namely, demand release and moral hazard. The empirical results show that: (1) URRBMI integration increases outpatient OOP costs, inpatient OOP costs, and total medical consumption, but it also releases the population's demand for medical care, which is meaningful at the initial stage of policy implementation. (2) The sources of the increase in medical costs are the release of medical demand and moral hazard. Specifically, for the low- and middle-income groups, the integration of URRBMI triggers an increase in medical costs mainly through the release of demand. For insured persons in the high-income group, URRBMI integration increases medical costs by triggering moral hazard issues. (3) URBMI integration changes the medical resource utilization behavior of the population, prompting the population to utilize higher-level medical resources more than primary care resources. (4) In addition, integration has a positive impact on residents' preventive medical care.